Assessing Irregular Warfare A Framework for Intelligence Analysis - Larson, Eric V. (RAND Corporation, 2008)
Provides an analytic framework and procedure for the intelligence analysis of irregular warfare (IW) environments that can serve as the basis for IW intelligence curriculum development efforts. Defines IW in terms of two stylized situations: population-centric (such as counterinsurgency) and counterterrorism. Provides a detailed review of IW-relevant defense policy and strategy documents and a list of relevant doctrinal publications.